Stain ESI menstrual red (Praxis Educativa, 2021)
The concerns presented in this article appeal to give an account, through biographical narratives, of the experiences felt by menstruating people when staining themselves in educational spaces. In this sense, the urgent need for a comprehensive menstrual education is addressed within the materials of Comprehensive Sex Education. In the search to demystify the normalizing and stereotyped discourses. The purpose then is to write and register the menstrual cycle in ESI. Stain ESI menstrual red. Of the blood that is not spilled by violence and that iterifies to be hidden. As if containing it were possible, menstruating bodies are required not to make visible the traces or records of their cyclical sexuality.
Keywords: menstruation; education; Comprehensive Sex Education